Admissibility and jurisdiction before the international criminal court regarding the Boko Haram situation in Nigeria - Quadri, Kafayat Motilewa; Eishan Jan, Mohammad Naqib; Abdul Wahab, Mohd. Iqbal; Ahamat, Haniff (UPM Press, 2015)
Terrorism is nothing new in present situations all over the world. Though there are different political manipulations of its definition, terrorism is a menace that affects the whole world at large. Boko Haram, a terrorist group based mainly in Nigeria started its first attack in 2004, and it has since been responsible for thousands of deaths of both Muslims and Christians in the country. The terrorist group is said to be demanding the adoption of the Islamic system of government and as a result has bombed many churches and schools. In 2011, the terrorist group attacked the United Nations Office in Abuja with the aid of one of its suicide bombers. The terrorist activities of Boko Haram in Nigeria have been under the purview and preliminary criteria known as preliminary investigations as carried out by the Office of the Prosecutor of the International Criminal Court since 2010. The Office of the Prosecutor came out with a report in 2013 that concluded there is a reasonable basis to believe that Boko Haram has been committing crimes against humanity of murder and persecution since July 2009. However, up until date, despite the abduction of over 300 schoolgirls by the terrorist group, the Nigerian government has not been able to bring the girls back or prosecute the perpetrators. When a State party to the Rome Statute has some form of armed conflict going on in its region, a referral may be made to the ICC to intervene. However, it must first be determined whether the crimes committed are those within the court’s jurisdiction and also whether the situation is admissible especially with regards to the complementary criteria as provided for in the Rome Statute. This paper will look into the admissibility of the Boko Haram situation and whether the International Criminal Court has jurisdiction over the crimes committed.